«New impoliteness» from the perspective of language games with swear words: T-shirt slogans - N. G. Bragina (Шаги, 2025)
The paper discusses obscene/associated with obscene, as well as explicit language used in T-shirt slogans. The pragmatic effect they produce is described. These inscriptions are defined as special speech acts. By wearing such a T-shirt, one becomes the addresser of an offensive statement and releases it into the public space. Some of the inscriptions could be considered as utterances that have abusive illocutionary force. They belong to counter-ethics. Others are associated with language games and could be attributed to counter-aesthetics. I examine the pragmatics of T-shirt slogans, and language games with swear words, such as abbreviation, neology, the use of polysemy, transliteration, contamination. The data (about 100 inscriptions) was collected from catalogues of online T-shirt stores. Most of the T-shirts are intended for women. This indicates a weakening of a double sociocultural taboo: the «unprintability» of swear words and the focus on male (rather than female) discourse. I define «the new impoliteness» as a type of communication that allows the use of swear words in a heterogeneous public environment. I focus on descriptions of physicality, cultural practices of body art, and the historical observation of prints on T-shirts, including swear inscriptions. Special attention is paid to the history of the word futbolka (T-shirt) and the history of T-shirt slogans with swear words.